The Internet Costsâ€™ Role in Indonesia's Creative Industry Competitiveness - Gigih Prihantono (JEJAK: Jurnal Ekonomi dan Kebijakan, 2022)
The purpose of this study is to analyze the role of the Internet as a soft infrastructure medium in the framework of international trade facilitation. as part of international trade facilitation which is expected to be able to reduce barriers in Indonesia's trade with 18 trading partners in the export of creative industry goods by HS codes: 49, 91, 92, 95 and 97. The analysis method usedÂ  is a quantitative approach with panel data regression using a gravity model based on time series data with cross sections of 18 trading partners from 2008 to 2017. The results of the analysis show that the internet subscription price variable has a significant effect on increasing international trade. Other variables such as GDP, population, and distance have a significant positive or negative effect on international trade, while FTA does not have any effect on exports of creative industry goods.